Nonsurgical management of gastroduodenal tuberculosis: Nine-year experience from a tertiary referral center - Dalal, Ashok; Puri, Amarender Singh; Sachdeva, Sanjeev; Sakuja, Puja (Endoscopy International Open, 2019)
Background and study aims Gastroduodenal tuberculosis (GDTB) is an uncommon disease. Surgery has been standard of care both for diagnosis and management of GDTB. The aim of this study was to evaluate the efficacy of non-surgical management of GDTB using a combination of anti-tuberculous therapy (ATT) along with endoscopic dilatation of the tuberculous stricture.Patients and methods Patients suspected to have gastroduodenal TB were evaluated: clinical, endoscopic, radiological, and histopathological data were recorded. Patients in whom a definite diagnosis of tuberculosis could not be confirmed on mucosal biopsies underwent endoscopic mucosal resection (EMR). Patients were treated with ATT and endoscopic dilatation was done if indicated. Patients were followed up to evaluate clinical, radiological and endoscopic response.Results Over a 9-year period from 2009 to 2017, 52 patients (mean age 28.5yrs) were diagnosed with GDTB. The most common presenting symptoms were vomiting (n = 51, 98 %) and weight loss (n = 52,100 %). The most common anatomical site of involvement was D1–D2 junction (n = 22, 42 %). Histopathological diagnosis could be made in 43 patients (82.6 %); 36 (69 %) on mucosal biopsies and in 7 of 10 patients (70 %) who underwent snare biopsy/EMR. Endoscopic dilatation was done in 37 patients (71 %) and median dilatation sessions were two. Failure of endotherapy occurred in four patients (7.6 %). All responders had complete amelioration of symptoms after 4 to 6 weeks of combination therapy. Median period of follow-up was 23.5 months and none of the patients reported any recurrence of symptoms.Conclusion ATT and endoscopic dilatation combined has a high success rate in management of GDTB and should be considered the standard of care.